MiR-584-5p potentiates vincristine and radiation response by inducing spindle defects and DNA damage in medulloblastoma - Nourhan Abdelfattah (Nature Portfolio, 2018)
The radiation and chemotherapy used for treating medulloblastoma patients cause debilitating side effects. Here, the authors show that miR-584 acts as a therapeutic adjuvant as it sensitizes medulloblastoma to radiation and chemotherapy by targeting HDAC1 or eIF4E3 to enhance spindle defects and DNA damage.